The Role of Neurosonology in the Diagnosis and Management of Patients with Carotid Artery Disease: A Review. Issue 3 (15th January 2018) - Kargiotis, Odysseas; Safouris, Apostolos; Magoufis, Georgios; Georgala, Maria; Roussopoulou, Andromachi; Stamboulis, Eleftherios; Moulakakis, Konstantinos G.; Lazaris, Andreas; Geroulakos, George; Vasdekis, Spyros; Tsivgoulis, Georgios
ABSTRACT: Carotid artery disease (CAD) is a common cause of ischemic stroke with high rates of recurrence. Carotid endarterectomy (CEA) or carotid artery stenting (CAS) are highly recommended for the secondary prevention of symptomatic CAD during the first 14 days following the index event of transient ischemic attack or minor stroke. CEA or CAS may also be offered in selected cases with severe asymptomatic stenosis. Herein, we review the utility of neurosonology in the diagnosis and pre‐/peri‐interventional assessment of CAD patients who undergo carotid revascularization procedures. Carotid ultrasound may provide invaluable information on plaque echogenicity, ulceration, risk of thrombosis, and rupture. Transcranial Doppler or transcranial color‐coded sonography may further assist by mapping collateral circulation, evaluating the impairment of vasomotor reactivity, detecting microembolization, or reperfusion hemorrhage in real time. Neurosonology examinations are indispensable bedside tools assisting in the diagnosis, risk stratification, peri‐interventional monitoring, and follow‐up of patients with CAD.